Training In Making Educational Posters Using The Canva Application for IPS Education Students FKIP Lambung Mangkurat University - Handy, Muhammad Rezky Noor; Mutiani, Mutiani; Ilhami, M. Ridha; Triyono, Sigit; Rusmaniah, Rusmaniah; Savitri, Siti Nur Laila (Universitas Lambung Mangkurat, 2024)
This article describes training in making educational posters using the Canva application for Social Sciences Education students, FKIP ULM. The method used in this article is community service activities carried out on March 13-14, 2024, at the Social Sciences Education Writing Laboratory FKIP ULM, then using 1) problem discovery observation stages, planning stages and implementation stages; 2) presenting data in the descriptive form; and 3) drawing conclusions based on activities to describe the research results systematically. In the results analysis section, the author uses literature studies to add insight, which is also supported by the results of interviews with training activity participants. Service activities are carried out in two activities. First, presentation and discussion related to making educational posters, from the definition to the steps in making a poster. Second, the practice of making posters via the Canva application by social studies education students using devices such as laptops and cellphones with a focus on the themes of ethnopedagogy and social studies education.